Environmental palaeogenomic reconstruction of an Ice Age algal population - Youri Lammers (Nature Portfolio, 2021)
Lammers et al. use sedimentary ancient DNA to reconstruct palaeogenomes of Nannochloropsis. This study demonstrates the value of sedaDNA for palaeogenomic reconstructions and population genomic analysis.